(untitled) (Historia, 2021)
Effects of urban development on former homelands need to be addressed after the period of urban transition. The article focuses on the evolution of a dispersed city settlement around Pietersburg. Three aspects are covered. Firstly, an outline is given of the apartheid legacy of developing a dispersed settlement system surrounding Pietersburg. Secondly, the post-apartheid local government restructuring of Pietersburg is described. Thirdly, the above historical findings are debated in the context of 'restructuring' Pietersburg after the transition to a new dispensation.